Respuesta :
Answer:
x = -6
Step-by-step explanation:
36 + x = 12 - 3x
36 + x - 36 = 12 - 3x - 36
x = -3x - 24
x + 3x = -3x - 24 + 3x
4x = -24
4x / 4 = -24 / 4
x = -6
Answer:
x = -6
Step-by-step explanation:
36 + x = 12 - 3x
We need all terms with x on the left side.
Add 3x to both sides.
36 + x + 3x = 12 - 3x + 3x
36 + 4x = 12
We need all terms that are just numbers on the right side. Subtract 36 from both sides.
36 - 36 + 4x = 12 - 36
4x = -24
We have 4x, which means 4 multiplied by x, on the left side. We want x alone. Divide both sides by 4.
x = -6